2014
DOI: 10.2217/epi.14.74
|View full text |Cite
|
Sign up to set email alerts
|

The CpG Island Methylator Phenotype in Breast Cancer is Associated with the Lobular Subtype

Abstract: These results depict a clear difference between genetically and epigenetically unstable breast carcinomas indicating different ways of tumor progression and/or initiation, which strongly supports the association of CIMP with the lobular subtype and provide new options for detection and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Since type 2 diabetes is a heterogeneous disease whose onset and progression depends on genetic and environmental factors, epigenetic mechanisms may also play a key role in the pathology of diabetes and its complications. DNA methylation (DNAm), the most studied epigenetic mechanism, has been associated with stable alterations of gene expression and implicated in the pathogenesis of type 2 diabetes and other age-related diseases [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Since type 2 diabetes is a heterogeneous disease whose onset and progression depends on genetic and environmental factors, epigenetic mechanisms may also play a key role in the pathology of diabetes and its complications. DNA methylation (DNAm), the most studied epigenetic mechanism, has been associated with stable alterations of gene expression and implicated in the pathogenesis of type 2 diabetes and other age-related diseases [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Also, several studies have compared MS-MLPA with MSP or pyrosequencing and showed a good concordance between MS-MLPA and these methods (Furlan et al, 2013[ 14 ]). Roessler and colleagues (2015[ 31 ]) recently studied genome-wide DNA methylation patterns for breast cancer subtypes using the Infinium Human Methylation 450k (HM450k) BeadChip. In general, this method is a proper tool to perform large-scale DNA methylation profiling.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, CIMP tumors had distinct epidemiologic characteristics, microsatellite instability (MSI) profile BRAF mutations and survival, compared to non-CIMP tumors [ 48 , 49 ]. CIMPs have been reported for a number of cancers, including upper aerodigestive tract (UADT) [ 32 ], oral cancer [ 50 ], and oesophageal squamous cell carcinoma [ 51 ] and breast cancer [ 19 ]. However, only single study was there in HNSCC, which explain CIMP in the sub-group of HPV (+) tumor of HNSCC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CIMP panel was classified into three groups: CIMP-high (at least 5 genes/loci methylated out of 10), CIMP-low (less 5/10 genes/loci methylated), and CIMP-negative (0/10 genes/loci methylated). This classification was done on the basis of the criteria previously used for CIMP status in other types of tumor [ 19 , 42 ]. Methylation index (MI) was also calculated for each case via dividing the number of Methylated genes/loci by the total number of gene/loci under study.…”
Section: Methodsmentioning
confidence: 99%